2011
DOI: 10.4061/2011/470607
|View full text |Cite
|
Sign up to set email alerts
|

A Biocompatible Nanocomposite for Glucose Sensing

Abstract: A nanocomposite containing amine functionalized multiwalled carbon nanotubes and a room temperature ionic liquid (1-butyl-3-methylimidazolium tetrafluoroborate) was prepared and applied for glucose oxidase (GOx) immobilization on glassy carbon electrode. The proposed nanocomposite provided a favorable microenvironment to preserve the bioactivity of GOx. It could also effectively facilitate the enzyme direct electron transfer to the electrode. This brought about a remarkable improvement in the sensitivity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Rahimi et al reported on a nanocomposite containing amine functionalized multiwall carbon nanotubes and 1-butyl-3-methylimidazolium tetrafluoroborate, a room temperature ionic liquid [ 95 ]. The composite was applied to glucose oxidase (GO x ) immobilization on glassy carbon electrode.…”
Section: Types Of Materials Used As Electron Mediators and Immobilizimentioning
confidence: 99%
“…Rahimi et al reported on a nanocomposite containing amine functionalized multiwall carbon nanotubes and 1-butyl-3-methylimidazolium tetrafluoroborate, a room temperature ionic liquid [ 95 ]. The composite was applied to glucose oxidase (GO x ) immobilization on glassy carbon electrode.…”
Section: Types Of Materials Used As Electron Mediators and Immobilizimentioning
confidence: 99%
“…On the basis of data from the World Health Organization (WHO) and the International Diabetes Federation, it is expected that the population of people with diabetes will double by the year 2045. , Therefore, careful management of diabetes can prevent acute complications and delay the progression of diabetes. Besides clinical diagnostics, quantification of glucose in other fields (e.g., the food and beverage industry, biotechnology, environmental protection, and agriculture) is also of great importance. , Among different techniques for glucose detection, electrochemical (bio)­sensors have attracted extensive attention as promising choices due to their superior features like low cost, simplicity, user convenience, fast response, and point-of-care detection capability. , Up to now, most of the glucose biosensors have been developed based on the immobilization of glucose oxidase and/or glucose dehydrogenase enzymes on a suitable substrate. Moreover, about 85% of the commercially available glucose biosensors are enzymatic electrochemical based sensors, which have advantages such as sensitivity and selectivity. ,, However, enzyme-based sensors suffer from some drawbacks including a complex and expensive enzyme purification process, low stability due to enzyme denaturation, and decreasing enzyme activity during the complicated immobilization steps. , In contrast, enzymeless electrochemical glucose sensors based on direct electrooxidation of glucose have become a research hot spot due to their low cost, simplicity, stability, easy modification, and, more importantly, freedom from oxygen limitations. , It is noticeable that the sensing material as the electrocatalyst has a significant role in designing nonenzymatic glucose sensors. Therefore, the development of efficient electrode materials with excellent catalytic activity, large surface area, and desirable morphology, size, shape, and composition is an essential factor in the construction of nonenzymatic glucose sensors. ,, Nanomaterials of carbon (like graphene, carbon nanotubes, boron-doped diamond), metals (Au, Zn, Ni, Cu, Pd), ,, metal oxides (ZnO, CuO), , alloys (PtPb, AuNi, NiNb), , and composites (carbon nanotubes/CuFe 2 O 4 , graphene oxide/Pd) , have been widely utilized as electrocatalysts in nonenzymatic glucose sensing.…”
Section: Introductionmentioning
confidence: 99%